CAPE: HISTORICAL PAST AND FASHIONABLE PRESENT - DITKOVSKA, Olesya; LUSHCHEVSKA, Olena; BUKHANTSOVA, Liudmyla (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper studies historical and modern models of women’s shoulder cape-type clothing, which has a long history and is a fashion trend of our time. A retrospective analysis of the types, shapes and varieties of cape decoration for the period from the 1750 to the early 1900 was carried out based on photographs of original cape models stored in museum funds. It has been established that during its history from a simple cape made of coarse cloth or wool from the end of the 18th century the cape, in addition to its direct purpose to protect from the cold, began to perform an aesthetic and informational function, as it received the status of an element of the wardrobe of the nobility and the wealthy segments of the population. For the elite, capes like a cape were sewn from expensive and luxurious fabrics, decorated with embroidery, ribbons, fringe, lace, jewellery, embroidered with cords, lined with fur, in order to emphasize the owner’s belonging to high society with all their appearance. It has been proven that historical clothes are relevant today and are an inexhaustible source of inspiration for modern designers who are subjects of different segments of the fashion system. Modern capes are extremely different from ancient models, have the greatest variety of types, shapes, options for stylistic embodiment than ever before. It is obvious that the "cape", as a design option for clothing, has gone beyond the concept of "shoulder cape" or "coat", and therefore should be considered an independent type of shoulder clothing. It has been established that by applying the principles of eclecticism through quotation, stylization or interpretation in costume design, it is possible to design an individual and unique image that will always create preferences for identifying its owner. A vivid example of this is the cape in the collections of world designers.